Desenvolvimento de novos complexos iônicos de paládio(II) derivados de bases de Schiff e aplicação na reação de Heck em água - Juliana Yurie Kadooca (2022)
Carbon-Carbon coupling reactions catalyzed by palladium are among the most important and used synthetic methodologies for the construction of organic molecular structures. The importance and relevance of these methodologies was recognized by the award of the 2010 Nobel Prize in Chemistry to the researchers, Heck, Negishi and Suzuki, who contributed greatly in this area. These reactions are usually carried out in anhydrous organic solvents, some of which are toxic, flammable and expensive. Contrary to these conditions, many alternatives have emerged, environmentally correct, using non-toxic and cheap means such as water, within the precepts of Green Chemistry. The use of water as a solvent in palladium-catalyzed reactions for C-C coupling is perhaps one of the most welcome catalytic methodologies in organic synthesis, combining efficiency, environmental awareness and reduced cost. In this work, fourteen ionic aldehydes were synthesized, two of them with anionic groups (sulfonate and carboxylic acid) and twelve with cationic groups, six with imidazolium site and six with triphenylphosphonium site, with yields between 65 and 99%. Once the aldehydes were obtained, they were subjected to a condensation reaction with o-phenylenediamine, obtaining fourteen imines with yields between 65 and 95%. These imines, in turn, were used as binders to obtain ionic palladium(II) complexes, using palladium(II) acetate as palladium source, with yields ranging between 67 and 92%. The obtained palladium(II) complexes were used as catalysts in Heck coupling, using water as solvent. Initially parameters such as base, surfactant, temperature and time were evaluated in order to establish the best reaction condition for the Heck reaction in water using bromobenzene and styrene as substrate. After that, the synthesized complexes were applied as catalysts in the coupling reaction and all the complexes showed a satisfactory catalytic activity of 54 to 100% of yield in obtaining the coupling product. Four palladium(II) complexes of ionic bis-amines, reduced analogues of ionic bis-imines were obtained with yield between 73 and 85%. Heck coupling catalysis tests with these complexes as catalysts provided yields between 48 and 85%, results close to those obtained using the bis-imine analogues.